I kunstkredse. Udvalgte biografiske romaner fra 90’erne - Haber-Biały, Justyna (Folia Scandinavica Posnaniensia, 2007)
The author presents four contemporary Danish biographical novels about female artists working in former historical periods. The analysis focuses on hterary visuaHzation of creative identity based on such aspects as: motives and strategies of artistic activity, the importance of creative autonomy, promoted concepts of arts. The aim of this analysis is to separate common motives, threads with reference to contemporary concepts of women's creative activity.